When Sovereign Investment Meets Banking Regulation: The Legal Implications of Danantara's Control over State-Owned Banks - Reka Dewantara; Tajwinder Singh (Journal of Religion, Local Politics, and Law, 2026)
The establishment of Danantara (Badan Pengelola Investasi Daya Anagata Nusantara) as the state investment holding introduces a new governance structure for Indonesia's state-owned banks, raising important questions about banking regulation, supervisory independence, and the public mandate of state-owned financial institutions. Existing banking legislation provides limited guidance on how this institutional arrangement should be reconciled with prudential banking principles and the established allocation of regulatory authority. This study examines the legal consequences of Danantara's controlling shareholding over Indonesia's Himbara banks through normative legal research employing statutory, conceptual, and comparative approaches. The analysis focuses on the interaction between corporate control, banking supervision, and financial governance within Indonesia's legal framework. The study finds that the current regulatory framework leaves unresolved issues concerning the separation between ownership and supervisory functions, the preservation of prudential governance standards, the institutional independence of financial regulators, and the public-service orientation of state-owned banks. These gaps create legal uncertainty regarding accountability and regulatory coordination in the governance of state-owned banking institutions. The article argues that these challenges require a differentiated regulatory approach that distinguishes policy-driven state ownership from conventional corporate control. It proposes a legal framework for policy-based controlling shareholdership to clarify the allocation of rights and responsibilities, and to establish regulatory safeguards applicable to sovereign investment holdings in the banking sector. This framework contributes to the broader discussion on sovereign wealth fund governance and banking regulation by offering a conceptual model that may guide future legislative and regulatory reforms in Indonesia